Corporate Income Tax Competition in the Caribbean - Ben Nassar, Koffie (IMF Working Papers; Working Paper ;, 2008)
Motivated by the concern that corporate income tax (CIT) competition may have eroded the tax base, this paper calculates average effective tax rates to measure the impact of CIT competition, including the widespread use of tax holidays, on the tax base for 15 countries in the Caribbean. The results not only confirm erosion of the tax base, but also show that CIT holidays must be removed for recent tax policy initiatives (such as accelerated depreciation, loss carry forward provisions, and tax harmonization) to be effective. These findings suggest that the authorities should either avoid granting CIT holidays or rely more on other taxes (including consumption taxes such as the value-added tax) in order to broaden the tax base.